Prevalence and risk factors for surgical site infection following equine colic surgery at the Onderstepoort Veterinary Academic Hospital, South Africa from 2013 to 2021 - Munoz, Juan (University of Pretoria, 2024)
Mini Dissertation (MSc (Companion Animal Clinical Studies))--University of Pretoria, 2024.